2020
DOI: 10.1371/journal.pone.0237998
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur availability modulates Arabidopsis thaliana responses to iron deficiency

Abstract: Among the mineral nutrients that are required for plant metabolism, iron (Fe) and sulphur (S) play a central role as both elements are needed for the activity of several proteins involved in essential cellular processes. A combination of physiological, biochemical and molecular approaches was employed to investigate how S availability influences plant response to Fe deficiency, using the model plant Arabidopsis thaliana. We first observed that chlorosis symptom induced by Fe deficiency was less pronounced when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Recently, Robe et al (2020) showed that, in Arabidopsis thaliana , the S deficiency-mediated negative regulation of the Fe uptake machinery might be induced to limit the unspecific transport into the root of potentially toxic divalent cations such as Mn and Zn by IRT1 (and other transporters like NRAMP1 ). Such findings highlight the importance to investigate the regulation of Fe/S interplay by considering the interaction of both Fe and S also with other essential nutrients.…”
Section: What Are the Reasons For The Crosstalk Between Sulfur And Iron Nutrition? Are There Common Signals Involved In Their Homeostasismentioning
confidence: 99%
“…Recently, Robe et al (2020) showed that, in Arabidopsis thaliana , the S deficiency-mediated negative regulation of the Fe uptake machinery might be induced to limit the unspecific transport into the root of potentially toxic divalent cations such as Mn and Zn by IRT1 (and other transporters like NRAMP1 ). Such findings highlight the importance to investigate the regulation of Fe/S interplay by considering the interaction of both Fe and S also with other essential nutrients.…”
Section: What Are the Reasons For The Crosstalk Between Sulfur And Iron Nutrition? Are There Common Signals Involved In Their Homeostasismentioning
confidence: 99%
“…Our results showed that both Fe and S deficiency induced Fe and S-responsive genes, respectively, indicating that plants perceived such deficiencies in our experimental conditions. The effect of S deprivation on Fe deficiency symptoms could be due to a differential accumulation of non-iron metals like Mn and Zn [ 2 ]. In Arabidopsis, the negative regulation (effect) of S deficiency on the Fe uptake machinery induced in response to Fe deficiency can be explained as a need of plants to limit the unspecific transport of potentially toxic divalent cations (Mn and Zn) into the roots through the activity of IRT1 and Nramp1 [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of S deprivation on Fe deficiency symptoms could be due to a differential accumulation of non-iron metals like Mn and Zn [ 2 ]. In Arabidopsis, the negative regulation (effect) of S deficiency on the Fe uptake machinery induced in response to Fe deficiency can be explained as a need of plants to limit the unspecific transport of potentially toxic divalent cations (Mn and Zn) into the roots through the activity of IRT1 and Nramp1 [ 2 ]. Here, we partially observed an effect of –S on Fe deficiency-induced genes: Fe/S interaction could occur in some species or developmental stage with specific mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations